A DISCOURSE ANALYSIS OF REFERENTIAL COHESION IN HANS CHRISTIAN ANDERSEN’S “THE LITTLE MATCH GIRL” - Dian Agustina Purwanto Wakerkwa; Aisyah Mutmainah (PT Akselerasi Karya Mandiri, 2025)
This study examined the use of reference as a cohesive device in Hans Christian Andersen’s fictional short story The Little Match Girl. The study aimed to describe the use and functions of referential items that help create continuity and unity throughout the text. The corpus of the story was analyzed through a qualitative descriptive approach based on Halliday and Hasan’s (1976) theory of cohesion in English. The analysis identified three main patterns of reference, with personal references occurring most frequently, followed by demonstrative and comparative forms. These three types of reference were used mainly to maintain focus on the main character, to establish spatial relationships, and to express contrast between the girl’s harsh reality and her imagined comfort. The findings indicated that cohesive reference played a central role in shaping the story’s emotional tone and narrative flow, thereby contributing to research on referential cohesion in literary discourse. The study suggests that raising learners’ awareness of referential cohesion can enhance their understanding of how meaning and continuity are constructed in written texts.